Mapping and national assessment of ecosystems and their condition in North Macedonia - Chobanova, Marija; Avukatov, Vasko; Atanasovska, Katerina; Melovska, Natalija; Brajanoska, Robertina; Shushlevska, Marjana; Jovanovska, Daniela; Trpeski, Vlatko; Jordanov, Sashko; Gicevski, Biljana; Sterijovski, Bogoljub; Nikolov, Lazar; et al. (Macedonian Journal of Ecology and Environment, 2024)
In 2020, North Macedonia conducted the first national assessment of ecosystem condition. The assessment fully adhered to MAES (Mapping and Assessment of Ecosystems and their Services) working group guidelines and represents the first implementation study in North Macedonia, marking it as the first Southeastern European country outside the EU to conduct such an assessment. National team of 30 experts was established and worked on accomplishment of the first two steps from the MAES operational framework: i) map of the ecosystem types and ii) assessment of their condition. Ecosystem typology corresponds to the MAES Level 2 categories, while the Level 3 categories were modified in order to fit our data. Mapping was done by using the available CORINE land cover data, published and unpublished scientific data, however major work was done with analyses of satellite imagery which resulted in a detailed map of country’s ecosystems. The ecosystem condition assessment was done for 15 natural and semi-natural ecosystem types. The anthropogenic and agricultural ecosystems were excluded from this assessment. Set of indicators was developed for each of the ecosystem types following MAES guidelines. In total, 16 indicators and 53 parameters were scored from 1 to 5 on specific scales. National and project data bases, as well as GIS tools were the main sources of data for the parameters. The majority of parameters were quantified, although some were evaluated based on their qualitative properties. It was followed by assessment on ecosystem services on national and local scale, accompanied by local scale implementation perspectives.